On the application of Ti/TiO2/CuO n-p junction semiconductor: A case study of electrolyte, temperature and potential influence on CO2 reduction - Brito, Juliana Ferreira de [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier, 2017)
This work presents the use of photoelectrocatalysis (PEC) aiming at converting CO2 into fuels such as methanol and ethanol. For the CO2 conversion, Ti/TiO2/CuO n-p junction semiconductor was chosen owing to its heterojunction benefits. The material was constructed using dip-coating technique and was found to present high porosity for both TiO2 and CuO deposits. Photocurrent vs potential curves showed a relatively good electrode photoactivity for CO2 dissolved in NaHCO3 subjected to UV–Vis commercial irradiation. The CO2 reduction process is found to be deeply affected by the type of electrolyte that, in essence, acts by supporting and generating different quantities of methanol, ethanol and acetone. Methanol is the preponderant fuel generated (91%) upon the reduction of CO2 by photoelectrocatalysis operating at UV–Vis light and +0.20ï¿½V as bias potential in 0.1ï¿½molï¿½L−1 K2SO4 and UV–Vis light irradiation. Interestingly though, under 0.1ï¿½molï¿½L−1 NaHCO3 pH 8 and applied potential of −0.6ï¿½V, we found it feasible to reach 97% for methanol following 2ï¿½h of reaction. The results primarily unravel an important contribution towards understanding the importance of the electrolyte when it comes to CO2 reduction by photoelectrocatalysis and Ti/TiO2/CuO electrode has clearly proven to be a promising material for the photoelectrochemical CO2 reduction into methanol with high selectivity.
Keywords: CO2 reduction; Fuels formation; p-n junction; Photoelectrocatalysis